Knowledge, Attitude, and Practices of Students Toward Global Warming - Fulmaran, Roselle (Journal of Interdisciplinary Perspectives, 2024)
The study aimed to determine the students’ knowledge, attitudes, and practices towards global warming and their relationships. The researcher utilized a descriptive-correlational design and the systematic sampling technique. The respondents of the study were 340 students from grades 7 to 12 at Sibulan National High School. The researcher used validated questionnaires and employed weighted mean, Spearman’s Rank Correlation Coefficient, mean, and percentage in treating the data. The study revealed that students’ knowledge about global warming is “very satisfactory.” Students’ attitude towards global warming is also “very positive” and their extent of practices to minimize global warming is “high.” Moreover, the study found that there is a significant and positive relationship between the students’ knowledge about global warming and their attitude towards global warming. The student’s attitude towards global warming is also significantly and positively related to their practices to minimize global warming. However, no significant relationship is found between students' knowledge about global warming and their practices to minimize it.